2006
DOI: 10.1016/j.ejcts.2005.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Hospital volume: operative morbidity, mortality and survival in thoracotomy for lung cancer.A Spanish multicenter study of 2994 cases

Abstract: No significant differences that do not favor the hypothesis that there is increased surgical risk and worse survival in centers having a lower volume were found in this Spanish multicenter study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 19 publications
0
22
1
1
Order By: Relevance
“…In Norway, as in other countries, lung cancer surgery is being centralised to high-volume hospitals despite the fact that the impact of hospital volume is still debated 25 26. This study could not corroborate a significant effect of hospital volume on postoperative mortality, although the OR at high-volume hospitals was more favourable.…”
Section: Discussioncontrasting
confidence: 65%
“…In Norway, as in other countries, lung cancer surgery is being centralised to high-volume hospitals despite the fact that the impact of hospital volume is still debated 25 26. This study could not corroborate a significant effect of hospital volume on postoperative mortality, although the OR at high-volume hospitals was more favourable.…”
Section: Discussioncontrasting
confidence: 65%
“…The surgical volume Several authors [331][332][333][334], although not all [335][336][337][338], have found an inverse relationship between surgical volume and post-operative morbidity and mortality rates, and even longterm survival of lung cancer patients.…”
Section: Quality Of Lung Cancer Surgerymentioning
confidence: 99%
“…Numerous studies dealing with the relationship of hospital volume to operative mortality after resection of lung cancer have been published, [6][7][8][9][10][11][12][13][14] In 1992, Romano and Mark 6 reported the outcome of 12,439 adults who underwent pulmonary resection through California hospital discharge abstracts between 1983 and 1986. Mortality was 4.2% after lobectomy and 11.6% after pneumonectomy.…”
Section: Discussionmentioning
confidence: 99%